Sie sind auf Seite 1von 4

# 10.

Locus
Solutions
Section A Substituting (3) into (2),
 x2 
1. Let A = ( x1 , y1 ) and P = (x, y). y = 4 + 2 
 64 
Since P is the mid-point of AB, we have
x2
 x1 + (−2) y= +8
 x = 2
16
 16 y = x 2 + 128
y = 1 6
y +
 x 2 − 16 y + 128 = 0
2
∴ x1 = 2 x + 2 and y1 = 2 y − 6
Since A = ( x1 , y1 ) is a variable point on C, (b) P is a parabola.
we have
x1 y1 = 8 3. Let the coordinates of P be (x, y).
∴ (2 x + 2)(2 y − 6) = 8 3x − 4 y + 9
= ( x − 3) 2 + ( y + 4) 2
2( x + 1) ． 2( y − 3) = 8 3 +4
2 2

( x + 1)( y − 3) = 2 2
 3x − 4 y + 9 
xy − 3x + y − 3 = 2   = ( x − 3) 2 + ( y + 4) 2
 5 
xy − 3 x + y − 5 = 0
(3 x − 4 y + 9) 2 = 25( x 2 − 6 x + 9 + y 2 + 8 y + 16)
∴ The equation of the locus of P is
9 x 2 − 24 xy + 54 x + 16 y 2 − 72 y + 81
xy − 3 x + y − 5 = 0 .
= 25 x 2 + 25 y 2 − 150 x + 200 y + 625
16 x 2 + 9 y 2 + 24 xy − 204 x + 272 y + 544 = 0
2. (a) Let the coordinates of P be (x, y).
  1
 x = 8  t −  ................(1)
  t 4. (a) Since A, B, C are collinear,

 y = 4  t 2 + 1  ...........(2) slope of AC = slope of BC
  t2  5 −1 5 − k
=
4−h 4−0
From (1),
4 5−k
1 x =
t− = 4−h 4
t 8
2
(4 − h)(5 − k ) = 16
 1 x2
20 − 5h − 4k + hk = 16
t −  =
 t 64
4 − 4k = 5h − hk
1 x2
t2 − 2 + 2 = h(5 − k ) = 4 − 4k
t 64
4(1 − k )
1 x2 h= .........(1)
t + 2 =
2
+ 2............(3) 5−k
t 64

1
(b) AP : AB = 1 : 3 (b) Let the coordinates of P be (x, y).
AP : PB = 1 : 2 x+2 2
= ( x − 2 2 ) 2 + ( y − 0) 2
Let the coordinates of P be (x, y). 12 + 0 2
0 ×1 + h × 2
x= (x + 2 2) 2 = (x − 2 2) 2 + y 2
1+ 2
2h x 2 + 4 2x + 8 = x 2 − 4 2x + 8 + y 2
=
3 y2 = 8 2x
3x
∴ h= ............(2)
2
k ×1 + 1× 2  y = mx + c..................(1)
y= (c)  2
1+ 2  y = 8 2 x..................(2)
k+2
= Substituting (1) into (2),
3
∴ k = 3 y − 2..........(3) (mx + c) 2 = 8 2 x

## Substituting (2), (3) into (1), we have m 2 x 2 + 2mcx + c 2 − 8 2 x = 0

3x 4 [1 − (3 y − 2)] m 2 x 2 + (2mc − 8 2 ) x + c 2 = 0..........(*)
=
2 5 − (3 y − 2) Since L is tangent to P, the discriminant of (*)
3x 4 (3 − 3 y)
= equals to 0.
2 7 − 3y
(2mc − 8 2 ) 2 − 4m 2 c 2 = 0
3x(7 − 3 y ) = 8(3 − 3 y )
4m 2 c 2 − 32 2 mc + 128 − 4m 2 c 2 = 0
x(7 − 3 y ) = 8(1 − y )
7 x − 3xy = 8 − 8 y 32 2 mc = 128
7 x + 8 y − 3 xy − 8 = 0 128
c=
32 2 m
2 2
Section B c=
m

 y = mx + c..................(1)
5. (a)  2 (d) Using the results of (a) and (c),
 x + y = 4................(2)
2

2 2
Substituting (1) into (2), ± 2 1+ m2 =
m
x 2 + (mx + c) 2 = 4 8
x 2 + m 2 x 2 + 2mcx + c 2 − 4 = 0 4(1 + m 2 ) = 2
m
(1 + m 2 ) x 2 + 2mcx + (c 2 − 4) = 0...........(*) m2 + m4 = 2
Since L touches C, the discriminant of (*) m4 + m2 − 2 = 0
equals to 0. (m 2 + 2)(m 2 − 1) = 0
∴ (2mc) 2 − 4(1 + m 2 )(c 2 − 4) = 0 ∴ m 2 = 1 or −2 (rejected)
4m c − 4(c − 4 + m c − 4m ) = 0
2 2 2 2 2 2
m = −1 or 1
m 2 c 2 − c 2 + 4 − m 2 c 2 + 4m 2 = 0 2 2
Substituting m = −1 into c = ,
c 2 = 4(1 + m 2 ) m
c = ±2 1 + m 2 we have c = −2 2 .

2
2 2 (d) Substituting A(6, 8) into the equation of P,
Substituting m = 1 into c = ,
m (6 − 3) 2 + (8 − 4) 2 = 3 2 + 4 2
we have c = 2 2 . = 9 + 16
∴ The equation of common tangent is = 25
y = x + 2 2 or y = − x − 2 2 . ∴ A lies on P.
P touches C at A.
8−0
6. (a) Substituting A(6, k) into the equation of C. Slope of OP =
6−0
6 2 + k 2 = 100
4
k 2 = 100 − 36 =
3
= 64 OA ⊥ L1
∴ k = 8 or −8 (rejected) 4
∴ Slope of L1 = (−1) ÷
∴ A = (6, 8) 3
3
=−
4
(b) Let B = ( x1 , y1 ) and P = (x, y).
Equation of L1 is
Since P is mid-point of AB, we have 3
6 + x1 8 + y1 y −8 = − ( x − 6)
x= , y= 4
2 2 4 y − 32 = −3 x + 18
x1 = 2 x − 6 , y1 = 2 y − 8 3 x + 4 y − 50 = 0
B ( x1 , y1 ) lies on the circle C.
∴ (2 x − 6) 2 + (2 y − 8) 2 = 100
(e) L1 // L2 ,
( x − 3) 2 + ( y − 4) 2 = 25
∴ Slope of L2 = slope of L1
∴ The locus of P is a circle with centre (3, 4) 3
4
Let the equation of L2 be
(c) C : x 2 + y 2 = 10 2 3
y = − x + k.
P : ( x − 3) 2 + ( y − 4) 2 = 5 2 4
Distance between centres Let D ( x 2 y 2 ) be the end point of diameter
,

= (3 − 0) 2 + (4 − 0) 2 AD.
The mid-point of AD is the centre of P.
= 9 + 16
x2 + 6
=5 = 3 , x2 = 0
2
Difference of the two radius = 10 − 5 y2 + 8
=5 = 4 , y2 = 0
2
∴ P touches C. ∴ D = (0, 0)
The tangent line L2 passes through (0, 0).
∴ k=0
3
∴ y=− x
4
 3
 y = − x...................(1)
 4
 x 2 + y 2 = 100............(2)

3
Substituting (1) into (2),
2
 3 
x 2 +  − x  = 100
 4 
9
x 2 + x 2 = 100
16
25 2
x = 100
16
16 × 100
x2 =
25
= 64
∴ x = −8 or 8
−3
When x = −8 , y = × (−8) = 6
4
−3
When x = 8, y = × 8 = −6
4
∴ The intersecting points are (−8, 6) and
(8, − 6) .